2002
DOI: 10.1007/s00247-001-0641-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of gastro-oesophageal reflux in children. Comparison between oesophageal pH and barium examinations

Abstract: We believe that 24-h oesophageal pH monitoring should be used as the first line of investigation for the diagnosis of GOR in all children regardless of the age group. Barium examinations can be reserved for patients below 1 year of age, those going for surgery and those with negative oesophageal pH monitoring results but strong clinical suspicion of GOR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
1
15
0
1
Order By: Relevance
“…Neither Al-Khawari et al found correlations between the severity of reflux in BS and the results of 24-h esophageal pH monitoring [26].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Neither Al-Khawari et al found correlations between the severity of reflux in BS and the results of 24-h esophageal pH monitoring [26].…”
Section: Discussionmentioning
confidence: 98%
“…The BS, the oldest diagnostic method used in this category, can evaluate the mu- cosal alterations and the anatomical abnormalities [22]; additionally, it can provide a good representation for classifying the severity of reflux [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Gastroesophageal reflux disease (GERD) is defined as a disorder of the distal esophagus, with frequent return of the gastric contents into the esophagus, asso-reasons the method is not being used in many services (14,15) . On the other hand, upper gastrointestinal (UGI) series is a low-cost, less invasive well tolerated and it is available at most medical/clinical assistance centers.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, upper gastrointestinal (UGI) series is a low-cost, less invasive well tolerated and it is available at most medical/clinical assistance centers. Additionally, UGI series can detect anatomical abnormalities associated with the present symptoms in the upper gastrointestinal tract, and is the conventional imaging method for the study of GERD (14,15) . The early diagnosis of GERD and associated complications in preterm newborns is of utmost importance as it allows better approaches for the treatment of such an entity, potentially shortening hospital stay length and reducing morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Estudios posteriores demostraron que su sensibilidad en la detección de RGE es baja, tanto en pacientes adultos como pediátricos, sin RADIOLOGIA DIGESTIVA el uso de maniobras de provocación y no permite diferenciar entre reflujos fisiológicos y patológicos (10)(11)(12) . Asimismo, se ha demostrado que el hallazgo de alteraciones anatómicas que expliquen los vómitos, es poco frecuente (13) y que no existe diferencia significativa en la frecuencia de hernia hiatal entre pacientes con y sin RGE diagnosticado con pH metría (70% y 63% respectivamente) (13) .…”
Section: Introductionunclassified